Metadiscourse markers in Dr. Zakir Naik's persuasive discourse - Alkhodari, Fatima Tamim; Hadina Habil, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The International speaker Dr Zakir Naik has been the target of many studies for his influential speeches. Analysing persuasive speeches can be tackled from different angles, amongst which is the functional markers of persuasion represented by the Metadiscourse markers. Dr Zakir Naik's persuasive speeches have never been analyzed from a metadiscourse perspective. This paper aims to investigate the types and functions of metadiscourse markers in Zakir Naik's speeches. After transcribing Zakir Naik's videos manually, the coding process was accomplished via NVivo software and Microsoft Excel. Applying Dafouz-Milne's (2008) categories in the codification process, the interpersonal and textual metadiscourse markers are revealed. In terms of interpersonal metadiscourse markers, commentaries have been chiefly employed, contributing to Naik's relation to the audience. In terms of the textual metadiscourse markers, logical markers showed the highest usage. Such markers help in connecting his various persuasion strategies and multi-argument to make them smoothly connected. This paper has found that, generally, Zakir Naik has effectively developed and promoted his arguments via the extensive use of various metadiscourse tools while establishing an excellent relationship with the audience to attain a continuous relationship. This paper also argues that a fruitful approach to explore the interpersonal and textual definitions of language is Dafouz- Milne's categorization of metadiscourse markers as a powerful methodological tool in discourse analysis.